Leveraging Self-Assessment to Enhance Students’ Simple Past Tense Skills at MTs Muhammadiyah Al-Haq Palu - Fajria, Fajria; Thamrin, Nur Sehang; Maghfira, Maghfira; Nadrun, Nadrun (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2025)
This study aims to explore the effect of self-assessment on grammar teaching and learning, by analyzing how students identify and correct errors related to the use of simple past tense in their own work. A quantitative approach was used in this study by using a quasi-experimental design. The sample was selected using purposive sampling technique. Data were collected through a test, which was divided into two: pre-test and post-test. The population in this study was the ninth grade of MTs Muhammadiyah Al-Haq Palu, where class IX C was the experimental group (n=21) and class IX B was the control group (n=18). Statistical analysis was performed using the Mann-Whitney U test due to the study data was not normally distributed. The results demonstrated that there was an increase in learning outcomes in the use of simple past tense in the experimental group, compared to the control group. It was shown by calculations using the SPSS 24 software system where the Sig (2-tailed) value = 0.000 < 0.05, which means that the null hypothesis is rejected and the alternative hypothesis is accepted. In summary, this study indicated that self-assessment has a significant impact on enhancing students’ ability in simple past tense. The findings offer a new perspective for students, teachers and future researchers in enhancing English language teaching and learning.